Risk Difference Analysis for Dry Eye Incident in State University of Surabaya Swimming Sub Laboratory - Dewi Masitoh (Universitas Airlangga, 2019)
Dry eye syndrome is one of the eye health risks frequently suffered by swimmers who swim without goggles. It is initiated by direct contact of eyes with irritants from the disinfection process in the swimming pool. The purpose of this study was to analyze risk differences of using goggles for dry eye syndrome in the Sub Laboratory FIO Surabaya State University (Unesa). This research was an observational with cross sectional study design. The results of statistical tests showed that there were significant differences between swimmers using goggles and without goggles (p = 0,000). An examination of water found that the level of residual chlorine was (<1 mg / l), pH (<7), and alkalinity (> 200 mg / l). It calls the needs for strengthen the precaution for the presence of chemical risks. The result showed that the parameters did not satisfy the requirements of Permenkes RI No. 32 of 2017 about Standard for Environmental Quality and Water Health Requirements for Sanitary Hygiene Needs, Swimming Pools, Solus Per Aqua, and Public Baths. It can be concluded that there are differences in the risk of dry eye syndrome between swimmers who used goggles and without goggles. Swimmers is recommended to wear goggles while swimming to avoid the risk of dry eye syndrome. Furthermore, managers need to monitoring pool water quality in to order comply with term and reduce the risk of dry eye syndrome.